2002
DOI: 10.3168/jds.s0022-0302(02)74184-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein Solubility on Nitrogen Losses from Lactating Dairy Cows and Comparison with Predictions from the Cornell Net Carbohydrate and Protein System

Abstract: This experiment determined the effects of dietary protein solubility on amount, form, and route of nitrogen loss in lactating Holstein dairy cows, and the ability of the Cornell Net Carbohydrate and Protein System (CNCPS) to accurately predict rumen microbial yield, serum urea N (SUN), milk urea N (MUN), and fecal N. Eighteen multiparous Holstein cows were assigned randomly to one of three dietary treatments that were similar in crude protein (17.7%) content but differed in their content of soluble intake prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
3
12
1
2
Order By: Relevance
“…The range of intakes in the current experiment are within the ranges reported by Haig et al (2002) and Leonardi et al (2003) for cows in mid to late lactation (b 190 DIM) offered diets balanced at an overall CP concentration of 160 to 180 g/kg DM and is comparable to the N intake value (618 g/d) reported by Mulligan et al (2004) for grazing dairy cows fed a high protein diet in mid-lactation. The lower CP content of the concentrate offered on the LC treatment had the effect of reducing N intake and PDIN supply compared to the HG and HC treatments even though herbage constituted a large proportion of the diet on all treatments.…”
Section: Blood Metabolites and Nitrogen Balancesupporting
confidence: 76%
“…The range of intakes in the current experiment are within the ranges reported by Haig et al (2002) and Leonardi et al (2003) for cows in mid to late lactation (b 190 DIM) offered diets balanced at an overall CP concentration of 160 to 180 g/kg DM and is comparable to the N intake value (618 g/d) reported by Mulligan et al (2004) for grazing dairy cows fed a high protein diet in mid-lactation. The lower CP content of the concentrate offered on the LC treatment had the effect of reducing N intake and PDIN supply compared to the HG and HC treatments even though herbage constituted a large proportion of the diet on all treatments.…”
Section: Blood Metabolites and Nitrogen Balancesupporting
confidence: 76%
“…In this experiment, although SIP and DIP contents of forage soybean silage were higher than those of wheat bran (Table 1), there was no difference in fecal N excretion between both diets. This result was inconsistent with result of Haig et al (2002). Van Soest (1994) described that as the concentration of acid detergent insoluble protein (ADIP) increased, total tract N digestibility decreased.…”
Section: Potential Of Forage Soybean Silage As a Protein Sourcecontrasting
confidence: 56%
“…Broderick (2003) reported that excretion of urinary purine derivatives increased as dietary CP was increased from 15.1 to 16.7% of diet DM, but no further increase was noted with an 18.4% CP diet. Haig et al (2002) found urinary purine derivatives excretion increased quadratically as RDP (expressed as soluble intake N) concentration of the diet increased. Crude protein concentration or degradation most often does not affect microbial N flow (Windschitl and Stern, 1988a;Calsamiglia et al, 1995;Cunningham et al, 1996).…”
Section: Discussionmentioning
confidence: 91%